1987
DOI: 10.1084/jem.166.1.283
|View full text |Cite
|
Sign up to set email alerts
|

In vitro mutagenesis at a single residue introduces B and T cell epitopes into a class I HLA molecule.

Abstract: We have studied the interaction of HLA class I antigens with alloreactive cytotoxic T lymphocytes and monoclonal antibodies using site-directed mutagenesis and expression of an HLA-Aw68.1 gene. Two mutants containing distinct substitutions at polymorphic residues near the NH2-terminal end of the alpha 2 domain were made. One mutant with substitutions at positions 95 and 97 corresponding to residues found in HLA-A2.1 showed no alterations in binding of HLA-Aw68- or HLA-A2-specific monoclonal antibodies, but was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Our collaborator, Peter Parham (Stanford), had shown that a MAb, PA2.1, recognized residue 107 of HLA-A2 and that the amino acid substitution of glycine (in all other HLA types) for tryptophan (in HLA-A2) accounted for the HLA-A2 specificity of the PA2.1 MAb (5, 7). We found that this single amino acid difference also accounted for the immunodominant epitope recognized by most allogeneic CTL (4,5). Site-directed mutagenesis of residue 107 from tryptophan to glycine resulted in a loss of most cell-mediated cytotoxicity directed at HLA-A2 (4).…”
Section: Hla Derived Peptidesmentioning
confidence: 88%
See 1 more Smart Citation
“…Our collaborator, Peter Parham (Stanford), had shown that a MAb, PA2.1, recognized residue 107 of HLA-A2 and that the amino acid substitution of glycine (in all other HLA types) for tryptophan (in HLA-A2) accounted for the HLA-A2 specificity of the PA2.1 MAb (5, 7). We found that this single amino acid difference also accounted for the immunodominant epitope recognized by most allogeneic CTL (4,5). Site-directed mutagenesis of residue 107 from tryptophan to glycine resulted in a loss of most cell-mediated cytotoxicity directed at HLA-A2 (4).…”
Section: Hla Derived Peptidesmentioning
confidence: 88%
“…CTL were used to define the important structures of HLA molecules involved in allorecognition (3,4). Synthetic peptides corresponding to CTL target sequences present in the HLA molecule were made and tested in CTL assays to see if they would inhibit or augment cytotoxicity (5,6).…”
Section: Hla Derived Peptidesmentioning
confidence: 99%
“…Using naturally occurring HLA molecules [12] and site-directed mutants [13][14][15][16] to define the regions of the HLA molecules recognized by allospecific CTLs, we demonstrated that peptides corresponding to defined sequences of the HLA-A2, HLA-B 17, and most recently HLA-B27 molecules can specifically inhibit allogeneic CTLs, and that this inhibition occurs by the peptide binding to the CTL. Since this inhibition is antigen specific, the peptides presumably block by binding to the TCR [11].…”
Section: The Mhc Peptide Tcr Interactionmentioning
confidence: 99%
“…4C, compare the two bottom panels). mAbs to ␤ 2 m (BBM1 and Namb-1) did not stain Daudi-A2 cells grown in the A; lanes 1-30) or chased for 120 min before lysis (B; lanes [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Aliquots of the lysates were incubated as indicated, either at 4°C (lanes 1-8, 17-23, 31-35, and [41][42][43][44][45] or at 37°C (lanes 9 -16, 24 -30, 36 -40, and 46 -50) …”
Section: W6/32-reactive Free Heavy Chains Are Receptive To Peptide Anmentioning
confidence: 99%
“…Human mAbs (40) were selected that are operationally alloantigen-specific on Daudi cells (specificities are noted, Daudi alleles boldface): GV5D1 (A1, A9; IgG), SN230G6 (A2, B17, B57, B58; IgG), VP5 G3 (A11, A25, A26, A66; IgM), TRA2G9 (Cw1, Cw3, Cw4, Cw*1402; IgM), BVK1F9 (B8; negative IgG control), and BVK 5B10 (B8; negative IgM control). Peptides GILG-FVFTL from the influenza virus matrix glycoprotein 58 -66 (M1-Flu58 -66, flu), and AAGIGILTV from the melanoma Ag Melan-A/MART-1 [27][28][29][30][31][32][33][34][35] (Mart) are two well-known HLA-A2 ligands displaying high and low affinity, respectively (41), and major T cell epitopes. The HLA-B27 ligand FRYNGLIHR was used as a negative control in in vitro assembly assays.…”
Section: Abs and Protein Biochemistrymentioning
confidence: 99%